Enhancing Arabic Language Learning Outcomes Through The Total Physical Response (TPR) Method - Syihamuddin, Hafif; Mubin, Khoirul (STIQ Amuntai, 2025)
Madrasah Aliyah Negeri (MAN) is an Islamic educational institution under the Ministry of Religious Affairs aimed at developing students' Arabic language skills. However, the dominant use of the lecture method has made students passive and less motivated, which impacts their learning outcomes. This study aims to enhance the learning engagement and outcomes of Class X students at MAN 1 Kota Metro through the implementation of the Total Physical Response (TPR) method. We conducted the research using a Classroom Action Research (CAR) approach, which involved two cycles and a sample of 16 students. The results indicate that the use of the TPR method is effective in improving both student engagement and learning outcomes. Student engagement increased from an average score of 5.37 in the first cycle to 8.5 in the second cycle, showing an improvement of 3.13%. Meanwhile, student learning outcomes improved from 66.5% in the first cycle to 76% in the second cycle, with a 9% increase. Based on these findings, the researcher recommends the use of the TPR method in Arabic language teaching to create an interactive and participatory learning environment, as well as to enhance student motivation and achievement.